2011
DOI: 10.1111/j.1365-2966.2011.18531.x
|View full text |Cite
|
Sign up to set email alerts
|

Host galaxy-active galactic nucleus alignments in the Sloan Digital Sky Survey Data Release 7

Abstract: We determine the intrinsic shapes and orientations of 27 450 types I and II active galactic nucleus (AGN) galaxies in the spectroscopic sample of the Sloan Digital Sky Survey Data Release 7 by studying the distribution of projected axial ratios of AGN hosts. Our aim is to study possible alignments between the AGN and host galaxy systems (e.g. the accretion disc and the galaxy angular momentum) and the effect of dust obscuration geometry on the AGN type. We define control samples of non‐AGN galaxies that mimic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 119 publications
3
52
0
Order By: Relevance
“…In this scenario, selection of Type II AGNs may result in a bias toward edge-on galaxies, and therefore a bias toward edge-on dual SMBH systems, assuming they are orbiting in the galaxy plane following a merger. Indeed, there is some evidence that Type II AGN host galaxies show a statistically significant deviation from random orientations, and may deviate toward edge-on systems (Lagos et al 2011).…”
Section: Spatial and Spectroscopic Biasesmentioning
confidence: 99%
“…In this scenario, selection of Type II AGNs may result in a bias toward edge-on galaxies, and therefore a bias toward edge-on dual SMBH systems, assuming they are orbiting in the galaxy plane following a merger. Indeed, there is some evidence that Type II AGN host galaxies show a statistically significant deviation from random orientations, and may deviate toward edge-on systems (Lagos et al 2011).…”
Section: Spatial and Spectroscopic Biasesmentioning
confidence: 99%
“…This is supported by Gandhi et al (2009) who showed in high spatial resolution ground-based photometry of nuclear regions in nearby AGNs that the AGN-produced mid-IR continuum appears almost isotropic and unaffected by Si-absorption. Furthermore, the inclination angle of the host galaxy may have a significant obscuring effect on the AGN emission (e.g., Malkan et al 1998;Matt et al 2000;AlonsoHerrero et al 2011;Lagos et al 2011). In particular, those AGNs presenting strong Si-absorption features are often found to be hosted in highly inclined and/or merging galaxies (Deo et al 2007(Deo et al , 2009).…”
Section: Evidence For Dust Extinction Arising In the Host Galaxy Of Cmentioning
confidence: 99%
“…high column density towards the nucleus), this may be a non-negligible fraction. Therefore, this work and others (i.e., Blanco et al 1990;Davies et al 2007) has some implications for the results of optical studies such as the results of Shen et al (2010) and Lagos et al (2011). Further investigation of this type of galaxies should be made using optical and NIR data.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that NGC 7172 was classified as an NHBLR galaxy (Lumsden et al 2001) probably due to the lack of collimated dust grains along the line of sight, supporting our thesis that the torus is almost face-on and the extinction comes from the host galaxy. Shen et al (2010) and Lagos et al (2011) show that there are more Seyfert 2 galaxies in edge-on host galaxies than Seyfert 1's and studying NGC 7172 in the optical yields a Seyfert 2 galaxy. However, a BLR may still be hidden behind the dustlane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation